The Diagnose of Pleura Effusion - Dima Fitri Hayuningrum (Global Health Science Group, 2020)
Pleura effusion is fluid accumulation which takes places between parietal and visceral pleura. This accumulation happens because of infection, malignancy, or inflammation at the parenchym of lungs or because of specifi organ(s) in body. In the diagnose of pleura effusion, it is important to seek the main etiologiy factor. In this article, author uses literature review method. In this writing, author uses 17 international article and 2 books which were published in 1972-220. The references author uses are collected by doing a literature searching in database NCBi with keywords pleural effusion, diagnosis, and examination and further filtered by range of publication in 2010-2020. This literature searching yielded 1235 articles with then 17 were picked from them. This writing uses systemic literature review methodthat include activities like collecting, evaluating, and development of information systematically. The result of this literature review is that in diagnosing pleura effusion, we need to start from collecting information by doing anamnesis, holding physical examination, laboratory examination, and pleura puncture.